Incidence of and factors associated with brimonidine allergy - Sunee Chansangpetch; Pattawee Pongpisitkul; Kongkiart Tipparut; Kitiya Ratanawongphaibul; Rath Itthipanichpong; Anita Manassakorn; Visanee Tantisevi; Prin Rojanapongpun (PLoS ONE, 2025)
Purpose This study examined the incidence of and the factors associated with brimonidine allergy, as well as its clinical characteristics and management strategies. Methods We conducted a retrospective review of brimonidine prescriptions and the medical charts of patients who were administered brimonidine between 2019 and 2020. The participants were divided into two groups according to the presence or absence of brimonidine allergy. Data on the demographic and clinical variables were collected for comparative analyses between the two groups. Results A total of 12,024 brimonidine prescriptions were administered to 2,850 patients. Brimonidine allergy’s incidence was 5.5% (157 out of 2,850 patients). The median time from usage to the onset of allergic signs and symptoms was 32 weeks (interquartile range, 15–72 weeks). Conditional multivariable logistic regression analysis showed that brimonidine allergy was associated with concurrent topical steroid use (odds ratio [OR] = 0.18; 95% confidence interval [CI], 0.04 to 0.87; p = 0.033), concurrent artificial tear use (OR = 3.07, 95%, CI, 1.36 to 6.93; p = 0.007), and concurrent tafluprost use (OR = 3.63, 95% CI, 1.04 to 12.63; p = 0.043. The patients mostly experienced redness of the eyes (73.8%) and itching (50.0%). Most patients discontinued brimonidine usage (98.7%). The symptoms and signs improved after a median of 5.5 weeks of treatment. Conclusions Approximately 5.5% of brimonidine users developed brimonidine allergy, which typically manifested at 32 weeks. Concurrent artificial tear and tafluprost use increased brimonidine allergy risk, whereas topical steroids’ concomitant use reduced the risk.